Lesson Study-based Microteaching Design in Early Reading Instructional for Prospective Elementary School Teachers - Titis Angga Rini; Bagus Cahyanto; Nindya Nurdianasari (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2024)
This study aimed to develop a lesson study-based micro-teaching design for prospective elementary school teachers in early reading instruction. This study utilized an instructional development method from Dick and Carey, comprising seven stages of research procedure. Data were collected through questionnaires, field notes, and documentation, and analyzed using descriptive quantitative and qualitative methods. In this study, a product successfully developed a lesson study-based micro-teaching design presented in video tutorials for teaching early reading in elementary school. The result shows that development of this micro- teaching design was successfully implemented and served as a guide for early reading instruction in the Indonesian Language Learning in elementary school course. Micro-teaching was developed as tutorial stages for early reading instruction, based on a process approach encompassing pre-reading phase, reading phase, and post-reading phase, combined with a lesson study approach for collaborative and reflective teaching practices.